UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI KEGIATAN PENYULUHAN BERBASIS KEBUTUHAN DI SMP IT NURUL A'LA - Naila Wardatun Najah; Jihan Naailah Iskandar; Nabilla Cahya Aulya; Anita Khoerunisa; Ratna Kurniasih; Kalyla Raffa Fadhilah; Muslim Haidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning motivation through needs-based counseling activities at SMP IT Nurul A’la, a school located in a pesantren environment. The problem identified is the low motivation of students toward formal education, as they tend to prioritize religious learning over academic activities. This study uses a qualitative descriptive approach through community service activities involving 13 students. The implementation was carried out in four stages: observation, program design, preparation, and implementation with evaluation using pre-test and post-test. The results showed an improvement in students’ understanding after the intervention. In the pre-test, only 30.8% of students were in the high understanding category (scores 90–100), while after the counseling, this percentage increased to 76.9% in the post-test. In addition, students became more active, confident, and engaged during the learning process. These findings indicate that needs-based counseling is effective in increasing students’ learning motivation and awareness of the importance of formal education, especially in a pesantren-based educational setting.